2021
DOI: 10.3389/fphar.2021.600296
|View full text |Cite
|
Sign up to set email alerts
|

Dezocine, An Opioid Analgesic, Exerts Antitumor Effects in Triple-Negative Breast Cancer by Targeting Nicotinamide Phosphoribosyltransferase

Abstract: Opioids are a potential adjuvant treatment for certain cancers; while they are primarily used to relieve chronic pain, these drugs may also affect cancer progression and recurrence. Dezocine is one opioid commonly used in China, but its effects on cancer cells are unknown. Here, we demonstrated the inhibitory effect of dezocine on triple-negative breast cancer (TNBC) cells, and determined the underlying molecular mechanism. We found that dezocine suppressed cell proliferation, migration and invasion, and induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“… 61–63 , 70 However, in vitro studies have found that dezocine directly inhibits the viability and migration of HepG2 and Hep 3B HCC cells in a concentration-dependent manner by inhibiting cellular oxyglycolysis and its malignant potential through the serine/threonine kinase 1 (Akt1)-glycogen synthase kinase 3 (GSK-3) pathway, 71 and they have found that dezocine exerts an antitumor effect by targeting nicotinamide phosphoribosyltransferase in triple-negative breast cancer. 72 Thus, these findings suggest that dezocine has direct antitumor effects in vitro. However, the mechanism and significance are still unknown.…”
Section: Dezocine Has Potential To Regulate the Clinical And Biologic...mentioning
confidence: 78%
“… 61–63 , 70 However, in vitro studies have found that dezocine directly inhibits the viability and migration of HepG2 and Hep 3B HCC cells in a concentration-dependent manner by inhibiting cellular oxyglycolysis and its malignant potential through the serine/threonine kinase 1 (Akt1)-glycogen synthase kinase 3 (GSK-3) pathway, 71 and they have found that dezocine exerts an antitumor effect by targeting nicotinamide phosphoribosyltransferase in triple-negative breast cancer. 72 Thus, these findings suggest that dezocine has direct antitumor effects in vitro. However, the mechanism and significance are still unknown.…”
Section: Dezocine Has Potential To Regulate the Clinical And Biologic...mentioning
confidence: 78%
“…Studies have shown that NAMPT is overexpressed in colorectal cancer, gastric cancer, and glioma and is used as an anticancer target [15][16][17][18][19]; however, it has not become a widespread target in AML treatment, mainly due to the genetic heterogeneity of AML. Therefore, the selection of AML with high sensitivity to the NAMPT inhibitor has become a key premise for choosing NAMPT as a therapeutic target for leukemia.…”
Section: Resultsmentioning
confidence: 99%
“…This could help to solve the current problem of the opioid crisis. Also, dezocine is finding use for cancer pain management in China due to its analgesic properties [5] as well as its potential tumor inhibition properties [15,16]. Dezocine has potential therapeutic value for neuropathic pain, without evidence of tolerance or dependence, as demonstrated in a rodent model of neuropathic pain [6].…”
Section: Discussionmentioning
confidence: 99%